Computational Procedure of Performance Assessment of Lifetime Index of Products for the Weibull Distribution with the Progressive First-Failure-Censored Sampling Plan - Ching-Wen Hong; Wen-Chuan Lee; Jong-Wuu Wu (Journal of Applied Mathematics)
Process capability analysis has been widely applied in the field of quality control to monitor the performance of industrial processes. In practice, lifetime performance index CL is a popular means to assess the performance and potential of their processes, where L is the lower specification limit. This study will apply the large-sample theory to construct a maximum likelihood estimator (MLE) of CL with the progressive first-failure-censored sampling plan under the Weibull distribution. The MLE of CL is then utilized to develop a new hypothesis testing procedure in the condition of known L.